Evaluación de riesgos laborales en una empresa metalmecánica bajo normas internacionales OHSAS 18001:2007 - Concha Oñate, Roberto Xavier (2008)
The study carried out in this document is the result of the application of the methodology described by the OSHAS 18001 standard for the evaluation of occupational hazards in a metal-mechanic factory, taking as a factor of study all potential sources of accidents in the workplace. The objective of this study is to identify the occupational hazards present in the metalworking industry, describe each of the identified hazards, evaluate the risks through the FINE method and, based on the general risk matrix, prioritize existing occupational hazards and mention them. according to its magnitude and relevance. For the development of this project was taken as reference of study, the Production Unit of metallic structures Tabacundo administered and operated by the Honorable Provincial Council of Pichincha. The lighting and noise levels found in this study are the result of measurements made in the factory and whose values ​​were compared with the maximum and minimum levels established by international standards, these values ​​are currently used as a reference in several countries of Latin America The OSHAS 18001 standard is a management system applicable to any company that wishes to create a preventive culture.